A novel assay that characterizes properdin function shows neutrophil-derived properdin has a distinct oligomeric distribution - Moore, Sara R.; Menon, Smrithi S.; Galwankar, Neeti S.; Khuder, Sadik A.; Pangburn, Michael K.; Ferreira, Viviana P. (Frontiers in Immunology, 2023)
Properdin acts as an essential positive regulator of the alternative pathway of complement by stabilizing enzymatic convertases. Identical properdin monomers form head-to-tail associations of oligomers in a reported 20:54:26 ratio (most often described as an approximate 1:2:1 ratio) of tetramers (P4), trimers (P3), and dimers (P2), in blood, under normal physiological conditions. Oligomeric size is proportional to properdin function with tetramers being more active, followed by trimers and dimers. Neutrophils are the most abundant granulocyte, are recruited to inflammatory microenvironments, and are a significant source of properdin, yet the ratio of properdin oligomers released from neutrophils is unknown. The oligomer ratio of neutrophil-derived properdin could have functional consequences in local microenvironments where neutrophils are abundant and complement drives inflammation. We investigated the oligomer properties of neutrophil-derived properdin, as compared to that of normal human sera, using a novel ELISA-based method that detects function of properdin in a way that was proportional to the oligomeric size of properdin (i.e., the larger the oligomer, the higher the detected function). Unexpectedly, neutrophil-derived properdin had 5-fold lower function than donor-matched serum-derived properdin. The lower function was due to a lower percentage of tetramers/trimers and more dimers, indicating a significantly different P4:P3:P2 ratio in neutrophil-derived properdin (18:34:48) as compared to donor-matched serum (29:43:29). Release of lower-order oligomers by neutrophils may constitute a novel regulatory mechanism to control the rate of complement activation in cellular microenvironments. Further studies to determine the factors that affect properdin oligomerization and whether, or how, the predominant dimers in neutrophil-derived properdin, assimilate to the ~1:2:1 ratio found in serum are warranted.